Etiological analysis of the children with non-specific chronic cough in Fuzhou area of Fujian province - Tang, Su-ping (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2011)
OBJECTIVE: Chronic cough in children is a common pediatric symptom with complex causes and its diagnosis is difficult; chronic cough affects the life of children in both physical and mental health and also learning. Therefore this study aimed to investigate the causes of chronic cough in children in Fuzhou area of Fujian province